2018
DOI: 10.1159/000486771
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Suppresses TGF-B1-Induced Cardiac Myocyte Myofibroblast Transformation by Inhibiting Smad2/3 and Rhoa Signaling Pathways

Abstract: Background/Aims: Hypoxia modulation of transforming growth factor (TGF)- β-induced signaling during myofibroblast transformation is dependent on the specific cell type. The purpose of this study was to explore the effects of hypoxia on myofibroblast transformation of TGF-β1-induced cardiomyocyte H9c2 cells. Methods: H9c2 cells were cultured for intermittent hypoxia treatment and TGF-β1 treatment. α-Smooth muscle actin (α-SMA) expression was examined by western blotting and immunofluorescence after treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Interestingly, this inhibitory effect of sI/R on the increase of α-SMA levels induced by TGF-β1 or spontaneous differentiation in CF has not been previously described. A similar effect has been observed in H9c2 cardiomyocytes and in corneal keratocytes, where hypoxia prevented the transformation to myofibroblasts induced by, an effect which was associated with changes in TGF-β1 signaling pathways [49,50]. Further studies are necessary to elucidate the effects of the A/D/N association on signaling pathways implicated in the effects of differentiation of CF to MCF induced by TGF-β1 after sI/R.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, this inhibitory effect of sI/R on the increase of α-SMA levels induced by TGF-β1 or spontaneous differentiation in CF has not been previously described. A similar effect has been observed in H9c2 cardiomyocytes and in corneal keratocytes, where hypoxia prevented the transformation to myofibroblasts induced by, an effect which was associated with changes in TGF-β1 signaling pathways [49,50]. Further studies are necessary to elucidate the effects of the A/D/N association on signaling pathways implicated in the effects of differentiation of CF to MCF induced by TGF-β1 after sI/R.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have demonstrated that α-SMA is elevated in leiomyoma compared to myometrium [38]. Yan et al also found that the expression of α-SMA was significantly increased at 5 ng/ml TGFβ1 compared with the control in cardiac myocyte H9c2 cells [39]. In addition, fibronectin mRNA expression was higher in leiomyoma than in autologous myometrium, and the increase caused by TGFβ3 was markedly higher than the one caused by TGFβ1 [9].…”
Section: Discussionmentioning
confidence: 92%
“…A recent study reported that in TGF-β treated malignant glioma, MTDH protein was increased via Smad2/3 phosphorylation [ 30 ]. In activated TGF-β/Smad signaling pathway, the p-Smad2 and p-Smad3 form oligomeric complexes with Smad4, translocated into the nucleus and regulated genes transcription [ 35 , 36 ]. However, in our study, we demonstrated that TGF-β treatment perform functions on translational regulation of MTDH rather than transcriptional repression.…”
Section: Discussionmentioning
confidence: 99%